PKM Pengembangan Keprofesian Berkelanjutan Melalui Desain Pembelajaran dan Soal Berbasis HOTS - Susanti, Dessi -; Rino, Rino; Padli, Padli; Armiati, Armiati; Rahmidani, Rose (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
Teachers of Accounting expertise at SMK Negeri 2 Kota Pariaman are unable to: 1) Design learning oriented to higher-order thinking skills, 2) Design questions with the HOTS category, 3) Designing questions in accordance with the rules of writing questions. The solutions offered are: 1) Training and workshops Designing learning oriented towards higher order thinking skills, 2) Training and workshops Designing questions with the HOTS category, 3) Training and workshops to design questions in accordance with the rules of writing questions. The approach method used is: 1) Using needs- based methods, the community service team entrusts educational evaluation experts to provide training and workshops, 2) Using the method of lecturing, question and answer, discussion, assignment, and demonstration. The results achieved are: 1) Most (60%) teachers of Accounting skills were produced learning designs that were oriented towards higher order thinking skills, 2) The result of the design of questions with the HOTS category by the majority (60%) of the teachers of Accounting expertise, 3) The result of the design of questions in accordance with the rules of writing questions by the majority (60%) of teachers of accounting skills teachers of SMK Negeri 2 Kota Pariaman.